Analysis of Risk Factors Affecting The Occurrence of Chronic Obstructive Pulmonary Disease in Indonesia - Nurul Layly Firdausi; Kurnia Dwi Artanti; Chung-Yi Li (Jurnal Berkala Epidemiologi, 2021)
Background: Chronic obstructive pulmonary disease (COPD) is a lung disease caused by the occurrence of airflow limitation in the lungs and also causes 60% of all deaths in Indonesia. Purpose: This study aimed to analyze the risk factors that affect the incidence of COPD in Indonesia. Methods: This study was conducted in July–August 2019 in Indonesia as an analytic research study with a cross-sectional design, using data from the Indonesia Family Life Survey-5. The sample consisted of respondents aged >15 years, giving a total of 34,231 respondents. Data analysis was partially carried out using the chi-square test to analyze the relationships between the variables. Results: The majority of respondents were female, were aged <40 years, and had a low level of education. Risk factors for the development of COPD included, among others, an age of >40 years (p = 0.02; PR = 1.20; 95% CI = 1.02–1.41), male gender (p = 0.01; PR = 1.26; 95% CI = 1.07–1.49), smoking (p = 0.01; PR = 1.22 ; 95% CI = 1.03–1.44), first smoking age < 40 years (p = 0.02; PR = 1.22; 95% CI = 1.03–1.44), residence in urban areas (p = 0.01; PR = 1.43; 95% CI = 1.20–1.70), being underweight (p = 0.01; PR = 2.17; 95% CI = 1.76–2.66). Conclusions: The risk factors that affect the incidence of COPD include being aged >40 years, being male, smoking, taking up smoking when aged <40 years, urban residence, and being underweight.